Psychosocial safety climate as a moderator of the moderators: Contextualizing JDR models and emotional demands effects - Loh, May Young; Idris, Mohd Awang; Dollard, Maureen Frances; Isahak, Marzuki (Wiley, 2018)
Psychosocial safety climate (PSC) is a facet-specific aspect of organizational climate that pertains to employees’ psychological health. We sought to deepen our understanding of how and when resources function by considering the role of PSC as a contextual factor for job demands-resources model. We explained this using two different mechanisms – PSC as a resource passageway (i.e., channelling, supplying, bolstering, complementing, compensating resources) or PSC as a safety signal (i.e., enabling resource use) effect. Using longitudinal data from 429 Malaysian health care workers from 53 teams and hierarchical linear modelling (HLM), we found team PSC was a stronger moderator of emotional demands than control or rewards on psychological health problems (emotional exhaustion and somatic symptoms), after controlling for the baseline outcomes. A three-way interaction of team PSC at Time 1 with demands and resources (rewards only) at Time 2 showed that PSC is able to moderate the moderation relationship of demands and resources. Specifically, PSC, as a resource passageway, is providing a range of resources, that likely to compensate and complement low rewards. Hence, when both PSC and rewards were low, emotional demands had the strongest effect on psychological health. This result is robust as it was validated using HLM and split samples of PSC at the upper level. Given the important contextual role of PSC as a ‘moderator of the moderators’, building PSC should be the focus of workplace interventions to protect the psychological health of workers. Practitioner points: Psychosocial safety climate may compensate for job resources, particularly rewards in an organization to protect workers’ psychological health. Psychosocial safety climate buffers the detrimental effect of emotional demands on workers’ psychological health better than rewards and control.